2021
DOI: 10.1371/journal.pone.0251754
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of in-hospital mortality in COVID-19; a prospective cohort study from Pakistan

Abstract: A prospective cohort study was conducted at the Indus Hospital Karachi, Pakistan between March and June 2020 to estimate the in-hospital mortality among hospitalized COVID-19 patients and its determinants. A total of 170 adult patients were enrolled and all-cause mortality was found to be 39% (67/170). Most non-survivors were above 60 years of age (64%) while gender distribution was quite similar in both groups (males: 77% vs 78%). Most (80.6%) non-survivors came with peripheral oxygen saturation less than 93%… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
37
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 38 publications
9
37
2
Order By: Relevance
“…We conducted this small-scale, retrospective study and analyzed risk factors among these patients. Nonsurvivors had a higher mean age compared to survivors, similar to other studies from Wuhan and Pakistan [7][8]. More than half of the patients had some underlying chronic illness, commonly hypertension followed by diabetes and hypothyroidism, similar to studies on Chinese and Italian patients [7,9].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We conducted this small-scale, retrospective study and analyzed risk factors among these patients. Nonsurvivors had a higher mean age compared to survivors, similar to other studies from Wuhan and Pakistan [7][8]. More than half of the patients had some underlying chronic illness, commonly hypertension followed by diabetes and hypothyroidism, similar to studies on Chinese and Italian patients [7,9].…”
Section: Discussionsupporting
confidence: 82%
“…The various other parameters were, however, almost similar in both groups. This is in conjunction with most other studies, thus signifying the role of these laboratory parameters in determining the severity of COVID-19 disease and the high rates of mortality [8,13,[17][18]. C-reactive protein and serum ferritin were elevated among non-survivors thus stressing the role of the inflammatory cytokine storm in the disease severity and poor prognosis [13].…”
Section: Discussionsupporting
confidence: 70%
“…Our findings revealed that elevated procalcitonin was most strongly associated with both mortality and ICU acceptance, thereby contributing to the growing body of evidence for the utility of procalcitonin in the context of COVID-19 infection [14,15]. Calcitonin is normally expressed in neuroendocrine cells, but its precursor, procalcitonin (PCT), has been identified as a unique biomarker specific for bacterial sepsis [16].…”
Section: Discussionmentioning
confidence: 56%
“…However, the overall mortality reported from another one of our recently published papers from this cohort was 39% which was not very different from the Remdesivir group here. 13 One important difference to highlight in our data is that Remdesivir was being administered to people at a median 10th day (IQR=8-11) of illness during the first wave of COVID-19. Later, published data indicated that this was probably already late.…”
Section: Discussionmentioning
confidence: 91%